If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + y + 2 = 7 Reorder the terms: 2 + 2y + y = 7 Combine like terms: 2y + y = 3y 2 + 3y = 7 Solving 2 + 3y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3y = 7 + -2 Combine like terms: 2 + -2 = 0 0 + 3y = 7 + -2 3y = 7 + -2 Combine like terms: 7 + -2 = 5 3y = 5 Divide each side by '3'. y = 1.666666667 Simplifying y = 1.666666667
| 2x+5=x-5 | | 10(v+1)-4v=3(2v+2)-11 | | -2z=6 | | 3x-12=2x-4 | | x^2-9x=3 | | -7y+12=47 | | 2y=24 | | x^2+8x-160=0 | | 21-u=-17 | | w^2+8w=0 | | 9+x=3-5x | | x+5y=20 | | 6x+13=12-5x | | 12-8x=84-29x | | 18n+29=-9(4-2n) | | -131-9x=7x+15 | | 8w=24 | | 12x-5x+280=14x | | 7+8x=13-3x | | 5(3x-4)=12+7x | | X+(3*-2)=-15 | | M-(-6)=11 | | 15(6c-1)-14=88c+15 | | 2z-8=-16 | | G+(-6)=7 | | 7x=12+4x | | 24x-7-16x+2=22x-5-14x+15 | | z+0=15 | | 4(x+7)=20 | | -6+s=11 | | 5x-3=-58 | | -3(1-3Y)-3Y=-15 |